Diagnostic value of mean platelet volume for neonatal sepsis: A systematic review and meta-analysis - Wang, Jingjing (Medicine (Baltimore), 2020)
BACKGROUND: An increasing number of studies in recent years have identified mean platelet volume (MPV) as a predictive marker for neonatal sepsis. However, most of these studies focused on single regions, and therefore, the findings remain inconclusive. We, in this study, aimed to evaluate the potential of MPV as a biological indicator of neonatal sepsis through a systematic review and meta-analysis. METHODS: We searched PubMed, the Cochrane Library, Embase, and WanFang database for articles on MPV and neonatal sepsis, published from January 1, 1990 to December 31, 2018. We included 11 studies on 932 neonates with sepsis in this meta-analysis. RESULTS: The overall meta-analysis showed that MPV was significantly higher in patients with neonatal sepsis compared with healthy controls. Subgroup analysis revealed that the type of diagnostic criteria, analyzer, analyte, and controls used in the studies affected the difference in MPV between patients and healthy controls. CONCLUSION: MPV was significantly higher in the neonatal sepsis group compared to the control group. Therefore, in clinical practice, MPV could be used as an indicator for the early diagnosis of neonatal sepsis.